Serum Lipids in Patients with Active Rheumatoid Arthritis And It's Relation to Drug Therapy - mad, Talal Abdulsa; Al-Zaidi, Ghazi T. (Journal of the Faculty of Medicine Baghdad, 2005)
Objective To detect the changes in serum Lipids among Iraqi patients with active Rheumatoid Arthritis (RA) and the effects of drug therapy.Patients and methods Fifty Iraqi patients with untreated active Rheumatoid Arthritis and 50 matched healthy control were studied with concentration on estimation of fasting serum Lipid profile which is repeated after 3month treatment with different disease modifying anti Rheumatic drugs (DMARDs) regimens.Results Fifty Iraqi patients were included in this prospective study 47 females (94%) and 3 males (6%). The mean age of patients was (45±3.20).fifty healthy individuals were included in this study as a control group 45 females (90%) and 5 males (10%) the mean age of the control group was (44.9±2.9).Our results showed a significant reduction of VLDL, LDL, HDL, serum cholesterol and serum triglyceride in-patients with active RA (p=